1999
DOI: 10.1006/viro.1999.0056
|View full text |Cite
|
Sign up to set email alerts
|

Possible Emergence of New Geminiviruses by Frequent Recombination

Abstract: Although exchange of genetic information by recombination plays a role in the evolution of viruses, the extent to which it generates diversity is not clear. We analyzed genomes of geminiviruses for recombination using a new statistical procedure developed to detect gene conversions. Geminiviruses (family, Geminiviridae) are a group of plant viruses characterized by a genome of circular single-stranded DNA (approximately 2700 nucleotides in length) encapsidated in twinned quasi-isometric particles. Complete nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
957
0
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,386 publications
(993 citation statements)
references
References 39 publications
18
957
0
18
Order By: Relevance
“…Interspecies recombination has played a major role in the evolution of members of ssDNA virus family Geminiviridae [24], whereas, in positive sense ssRNA viruses, it has been reported in the Potyviridae [25] and Luteoviridae [26]. Interspecies recombination analysis in the current study revealed the lack of extensive exchange of genetic material from other Carlavirus species to GarCLV, but still, provided an evidence for interspecies recombination events in the CP gene of 22 Carlavirus species (Suppl.…”
mentioning
confidence: 47%
“…Interspecies recombination has played a major role in the evolution of members of ssDNA virus family Geminiviridae [24], whereas, in positive sense ssRNA viruses, it has been reported in the Potyviridae [25] and Luteoviridae [26]. Interspecies recombination analysis in the current study revealed the lack of extensive exchange of genetic material from other Carlavirus species to GarCLV, but still, provided an evidence for interspecies recombination events in the CP gene of 22 Carlavirus species (Suppl.…”
mentioning
confidence: 47%
“…A total of seven methods were applied, including GENECONV,46 RDP,47 Chimaera,48 SiScan,49 3Seq,50 MaxChi,51 LARD 52. Recombination had to be confirmed by at least four of the seven methods with p value cut‐off of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Recombination Detection Program (RDP v4.43) [45] was used to identify potential recombination events through different models. In this study, three methods were used to analyze the sequence: RDP [46], GENECONV [47], and MaxChi [48]. The highest acceptable p value is 0.05 with 100 times of permutation and shuffled alignment columns.…”
Section: Detection Of Recombination Events In P2x Genesmentioning
confidence: 99%
“…To understand the evolutionary feature of P2X genes, recombination points were investigated using the RDP software with the RDP [46], Geneconv [47], and MaxChi [48] methods. As shown in Table 3, a total of 116 intragenic recombination events were identified, 64 identified using RDP, 10 using GENECONV, and 42 using MaxChi.…”
Section: Detection Of Intragenic Recombination Events In the Putativementioning
confidence: 99%